Metabolic and Biochemical Responses of Juvenile Babylonia areolata to Hypoxia Stress - Baojun Tang; Xiaoyao Ren; Zhiguo Dong; Hanfeng Zheng; Yujia Liu; Tao Wei (Biology)
As an important aquaculture species, the marine snail Babylonia areolata is frequently subjected to fluctuation in dissolved oxygen concentration during farming and transportation processes. In the present study, we investigated the metabolic rates, transcription, and enzyme level responses of juvenile B. areolata exposed to long-term stress (144 h). The results showed that the mortality rate of juvenile B. areolata was higher in the 0.5 mg O2/L group compared to the 2 mg O2/L group. During the hypoxic stress period, both oxygen consumption and ammonia excretion rates were observed to be lower in juvenile B. areolata than those in the control group. As hypoxic stress duration prolonged, juvenile B. areolata demonstrated significantly elevated activities of pyruvate kinase (PK) and alkaline phosphatase (AKP), alongside reduced activities of lactic dehydrogenase (LDH), acid phosphatase (ACP), and superoxide dismutase (SOD). Significant changes in the expression levels of PK and LDH genes were observed during the hypoxic stress. The expression levels of ACP and SOD genes were significantly downregulated, while juvenile B. areolata exhibited elevated AKP gene expression levels under 0.5 mg O2/L. Our findings suggest that under long-term exposure to hypoxia, B. areolata failed to maintain energy homeostasis and suffered biochemical disruptions, leading to a reduction in survival. The mortality rate of B. areolata can be substantially decreased by ensuring that transportation time does not exceed 48 h.